Latihan fisik tenis melayani kinerja pada remaja: Tinjauan sistematis - Sahib Saleh, Muhammad; Arif Saleh, Hasbunallah; Nurkadri, Nurkadri; Suharta, Asep; Syahrul Saleh, Muhammad (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Physical training on improving court tennis service skills in adolescent athletes is one part of mastering skills for teenagers. However, not all exercises that have been done by teenagers can be successful in mastering tennis serve skills. The main objective of this study is to explain physical training to support service skills in tennis. This study follows the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) and Meta-analysis. Scientific articles are obtained from Elsevier, Pubmed, Science Direct, Web of Science, National Index, Google Scholar, and Journal of Sports Coaching. After following the exclusion criteria, only 8 articles remain. The review successfully showed that most research, and quantitative approaches are the methods and types of research used. One important aspect of physical training is support for service skills on the tennis court. The practice study program lasts 3 weeks to 12 weeks. They do one to > two days per week. Conclusion The findings suggest that physical exercise can increase the speed of tennis serves. Recommended physical exercises to improve tennis serve include Exercises, Core Legs, Stability, and Arms. Further research can be continued by mapping research analysis on this topic using other methods to explore various forms of exercises for mastering skills in sports. This literature review can also be continued by discussing other topics related to mastery of skills.